Socioeconomic Inequalities in Children Health in MENA Countries - Wang, Kunyu (Université d'Ottawa | University of Ottawa, 2013)
It is always concerned that there are large inequalities in the child health sector between rich and poor, especially in the developing countries. The purpose of this paper is to examine child health inequality and the child health achievement in six Middle East and North Africa countries, with particular attention being paid to the relative contribution of each category of health attributes to total socioeconomic health inequality and to the deviation from perfect health within each country. We address this question with the use of Makdissi, Sylla and Yazbeck (2012)’s counting approach and decomposition approach to capture the socioeconomic inequalities in children health. Data comes from the Demographic and Health Surveys (DHS) and the United Nations Children's Fund (UNICEF).